External Shocks on a Dollarized Economy: An Empirical Evidence From Ecuador - Zambrano Córdova, Elena (2019)
Theory suggests that countries within a dollarized regime will have problems responding to external shocks, since these countries lack of monetary policy. Empirical research on this issue is based mainly on the case of Panama, as the country adopted dollarization in 1904. However, since 2000 Ecuador, a very vulnerable economy to external disturbances through its dependence on oil exports and personal remittances, adopted the regime as well. In order to contribute to the empirical evidence about one disadvantage of the dollarized regime, this work examines how changes in terms of trade and personal remittances a朽ect the economy of Ecuador in comparison to the other dollarized and non-dollarized countries in the  region. The aim is to test if whether external shocks result in greater costs to the Ecuadorian economy. Performing an EGLS panel model, the indings suggest that these externals shocks have not led to major repercussions to Ecuador in  comparison with the entire region. Furthermore, within the dollarized countries, changes in terms of trade leads to higher costs to Panama and El Salvador than to Ecuador. Furthermore, between these two countries and, even the overall region, a “resource curse” seems to be present.